Anhydrides as α,β-unsaturated acyl ammonium precursors: isothiourea-promoted catalytic asymmetric annulation processes - Robinson, Emily R. T.; Fallan, Charlene; Simal, Carmen; Slawin, Alexandra M. Z.; Smith, Andrew D. (Chemical science (Cambridge), 2013)
The asymmetric annulation of a range of alpha , beta -unsaturated acyl ammonium intermediates, formed from isothiourea HBTM 2.1 and anhydrides with either 1,3-dicarbonyls, beta -ketoesters or azaaryl ketones gives either functionalised esters (upon ring opening), dihydropyranones or dihydropyridones in good yields (up to 93%) and high enantioselectivity (up to 97% ee).